The effects of a harness safety system during maximal treadmill run testing in collegiate middle- and long-distance runners - Mermier, C. M.; Zuhl, M. N.; Wilmerding, M. V.; Beam, J. R.; White, A. C.; Salgado, R. M.; Beverly, J. M. (The Journal of Strength and Conditioning Research, 2013)
This study compared the results of graded maximal treadmill testing with and without a safety harness (SH) spotting system among collegiate middle- and long-distance runners. Thirteen (n = 8 men, n = 5 women) collegiate runners completed 2 randomly selected maximal treadmill tests. One trial used an SH, and one trial used no harness. All tests were separated by at least 48 hours. The subjects began the test at a velocity of 14.5 or 12 km/h with 1% grade for men and women, respectively, and increased 0.80 kilometers/hr per stage. During each trial, metabolic data and running speed values were recorded along with the completion of a safety questionnaire. No significant difference was found for maximal oxygen consumption (60.84 ± 8.89 vs. 60.733 ± 9.38 ml/kg/min) and velocity at maximal oxygen consumption (5.33 ± 0.62 vs. 5.24 ± 0.57 m/s) between the no harness and harness trials, respectively. Test time was found to be significantly longer in the no harness trial (611.06 ± 119.34 vs. 537.38 ± 91.83 seconds, p < 0.05). The results of the safety questionnaire demonstrated that the runners felt significantly more comfortable during the SH trial (p < 0.05).